PEMBUATAN DAN UJI STABILITAS SABUN PADAT EKSTRAK DAUN PETAI CINA (Leucaena leucocephala) DAN SERAI (Cymbopogon citrates) DENGAN PENAMBAHAN EKSTRAK PANDAN (Pandanus amaryllifolius) - Puspita, Rika; Handayani, Reti Puji; Jenta Puspariki; Puspariki, Jenta (Sekolah Tinggi Ilmu Kesehatan Holistik, 2023)
Background: Chinese petai is a plant that is considered not to have any properties. But actually has many health benefits. There are many solid soap preparations that contain Chinese petai leaves but the aroma is lacking so it needs to be developed by adding additional aromas to increase attractiveness. Objective: This study aims to make a solid soap formula based on Chinese petai leaf extract, lemongrass extract and pandan extract which is stable in organoleptic storage. Methods: The design of this research is action research that aims to solve a problem by using processes such as planning, action, observation, and reflection. This study used Chinese petai leaf extract, lemongrass extract and pandan leaf extract obtained by the maceration method. Solid soap preparations were made with various formulas, including F1 without the addition of pandan extract, F2 with the addition of 1% pandan extract, F3 with the addition of 2% pandan extract. Results: The results of the organoleptic study showed no changes in either F1, F2 and F3. In the observation of the pH test, pH 7 was obtained for the three formulas. The drying shrinkage test also obtained results that met the simplicia standard. Meanwhile, for the preference test, it was found that F2 was the most popular formula in terms of color 55%, aroma 45%, and form 100%. Conclusion: The conclusion from this study is that the solid soap preparation is stable for 3 weeks of storage and the preference test shows that F2 with the addition of 1% pandan extract is more preferred by the respondents